The seven grand challenges in arachnid science - Kuntner, Matjaž (Frontiers in Arachnid Science, 2022)
This perspective identifies the grand challenges in arachnid science: 1. Grasp the arachnid species diversity. There is a need to accelerate taxonomic research to obtain a sense of arachnid species diversity, however, at the same time, taxonomy needs to increase its quality, rigor, and repeatability. 2. Standardize arachnid systematics research. A solid phylogenetic definition and morphological diagnosis of Arachnida and its composing subgroups, usually treated at the rank of order, are needed. Studies should aim to stabilize and standardize phylogenetic efforts at all levels of hierarchy, and systematists should adopt criteria for higher level ranks in arachnid classification. 3. Interpret arachnid trait evolution through omics approaches. Among the field’s grand challenges is to define the genetic diversity encoding for the diverse arachnid traits, including developmental, morphological and ecological characteristics, biomaterials such as silks, venoms, digestive fluids, or allergens and bioproducts that cause diseases. Comparative genomics, transcriptomics, and proteomics will provide the empirical basis for biotechnology to modify arachnid genomes to fit numerous applications. 4. Facilitate biotechnological applications of arachnid molecules and biomaterials. Among the grand field challenges is to define potential applications of arachnid bioproducts from therapeutics to industry. New natural and biodegradable products, e.g. from spider silks, should ease our burden on ecosystems. 5. Utilize arachnids as models in ecological and biogeographic research. Biodiversity inventory sampling and analytical techniques should be extended from spiders to other arachnid groups. Spiders and their webs could be used as environmental DNA samplers, measuring or monitoring ecosystems’ overall biodiversity. Arachnids are excellent models to address biogeographical questions at the global to local scales. 6. Disentangle evolutionary drivers of arachnid diversity. Among the field grand challenges is a more precise evaluation to what extent the emergence of arachnid phenotypes is shaped by classical selection processes, and under what conditions, if any, sexual conflict needs to be invoked. 7. Define effective conservation measures for arachnids in the light of global changes. Effective conservation measures in arachnology should integrate the data from phylogenetic diversity, physiology, ecology, biogeography, and global change biology.